Internety się palą. O wybranych semiotyzacjach pożaru katedry Notre Dame - Jankowska , Małgorzata (Załącznik Kulturoznawczy, 2019)
The aim of the article is to analyse some online reactions to the Notre Dame fire, especially the content of social media. The fire has often been interpreted through biblical symbolism as a sign of God’s presence, a warning or even a punishment. At the same time, various information bubbles have used the opportunity to discuss some basic global issues, e.g. climate change, comparing the burning cathedral to the burning Siberian and Amazonian forests. There are also some examples of the pure netlore which can be seen as an element of the process of carnivalization – a way out from the apocalyptic narratives of any kind.